PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 008 SUAK TEMENGGUNG KECAMATAN PEKAITAN KABUPATEN ROKAN HILIR - Muhamad Kholil; Zetra Hainul Putra; Hendri Mahardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the findings in class III SDN 008 Suak Temenggung, students’ learning results are still low in science subjects, from 22 students only 40.90% of students who scored above the Minimum Completeness Criteria (KKM) while 59,10% of students have not reached the KKM. This research is a classroom action research, carried out by two cycles. Application of Contextual Teaching and Learning approach aims to improve the science learning result of third grade students of SDN 008 Suak Temenggung. The instrument of this research can be seen in the activity score of students and teachers who have increased activity and students’ learning results. Activity of students in the first cycle of first meeting is 56.25% with sufficient category, and then at the second meeting is 62.50% with sufficient category. Students’ activity in the second cycle the first meeting is 81.25% with the very good category, and 87.50% in the second meeting with very good category. Teachers’ activity in cycle I at the first meeting is only 50% with the category of less and 56.25% in the second meeting with sufficient category. Teacher’s activity at the first meeting of the second cycle is 75.00% with the good category, and the second meeting of the second cycle 87.50% with the very good category. Application of contextual approach can improve students’ science learning outcomes from a base score with an average 60.68, has increased the value of daily tests in the first cycle with an average of 67.72, with 72.72% classical completeness, subsequently increase even more in the cycle II with an average of 73.18, with a 100% classical completeness. From the above discussion that the application of contextual teaching and learning approach can improve science learning result of third grade students of SDN 008 Suak Temenggung Rokan Hilir.Keywords: Contextual Teaching Learning Approach, Science Learning Result